Stacey Jacobs: capstone - Jacobs, Stacey, artist (Colorado State University. Libraries, 2015)
The artist's statement: I am a mother, wife, sister, daughter and friend - but most of all I am a graphic designer. My work as a graphic designer, has really defined the person I am. Designing is something that is inside of me. Good design has always been something that I have been drawn too. I've always enjoyed noticing different logos and storefront designs for businesses. I grab mailers as they come in and I am enveloped in the design. I am attracted to good design within so many things; including clothing, labels on drinks and also food items. Sometimes I even pick the ones that I liked the best based on that design. (Not always the best rule of thumb!) Design is all around us - in and on everything, and my design is a culmination of years of absorbing those wonderful pieces and emotions. I am modern and classic at the same time. I can produce vintage designs, organic pieces, and sometimes like to air on the side of grunge. I relish in making announcements or invitations, I love branding a new client or rebranding an old, and I thoroughly enjoy working on marketing and advertising. I am both humbled and grateful when I see something that I have accomplished be published. My work is constantly evolving, and I believe this has to do with my ever-changing life and learning from individuals and experiences, and my eye for good design that is all around. I am Stacey Jacobs.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.